Turning point for European Agricultural Policy? The agricultural negotiations of the Uruguay Round - Stephan Cramon-Taubadel; Ralf Kühl (Intereconomics, 1990)
Agriculture is undoubtedly the most important and controversial topic in the ongoing Uruguay Round of the GATT. Can a compromise between the divergent positions of the EC and the USA on agricultural trade be found? Does the Uruguay Round mark a turning point for the EC's Common Agricultural Policy?
Keywords: 330; Agricultural Trade